The Evolution and Biogeography of Wolbachia in Ants (Hymenoptera: Formicidae) - Manuela O. Ramalho; Corrie S. Moreau (Diversity, 2020)
Wolbachia bacteria are widely distributed across invertebrate taxa, including ants, but several aspects of this host-associated interaction are still poorly explored, especially with regard to the ancestral state association, origin, and dispersion patterns of this bacterium. Therefore, in this study, we explored the association of Wolbachia with Formicidae in an evolutionary context. Our data suggest that supergroup F is the ancestral character state for Wolbachia infection in ants, and there is only one transition to supergroup A, and once ants acquired infection with supergroup A, there have been no other strains introduced. Our data also reveal that the origin of Wolbachia in ants likely originated in Asia and spread to the Americas, and then back to Asia. Understanding the processes and mechanisms of dispersion of these bacteria in Formicidae is a crucial step to advance the knowledge of this symbiosis and their implications in an evolutionary context.